Small Arms Control Policies in Latin America - Sanjurjo-García, Diego (2021)
This article provides a general and updated overview of small arms control policies in Latin America. In order to strike a balance between their legitimate use and the prevention of social harm, all Latin American states regulate the possession and use of firearms. A comparative analysis shows that there is a wide heterogeneity between countries, but most do so in relatively restrictive ways and with rigorous licensing and registration systems. Nevertheless, limited compliance with the law and the lack of empirical evidence on their impact make it difficult to evaluate their results. Ultimately, it is not possible to determine whether these policies prevent injuries and deaths, in line with an area of public policy in which important evidence is still missing.